2018
DOI: 10.17979/reipe.2018.5.2.4421
|View full text |Cite
|
Sign up to set email alerts
|

Alumnado rechazado por sus compañeros en Educación Infantil: prevalencia, diferencias de género y relación con problemas externalizados || Children rejected by their peers in Kindergarten education: Prevalence, gender, differences and association with externalizing problems

Abstract: Una de las claves para un desarrollo psicosocial saludable es tener amigos y sentirse aceptado por las personas que para uno son significativas. Sin embargo, existe un porcentaje significativo de estudiantes que son rechazados por sus iguales, lo cual puede conllevar importantes consecuencias negativas para su bienestar y desarrollo. Las causas por las que un alumno puede ser rechazado son variadas. En este estudio se explora específicamente la relación entre agresividad y rechazo. El presente trabajo, por tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This study found that 9.7% of students suffered peer rejection, which is a similar percentage to that found in other studies on infant education [11]. A total of 90.3% of the children who suffered rejection are boys [16], and we found that girls were more popular than boys; 60.7% compared to 39.3% [15,16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that 9.7% of students suffered peer rejection, which is a similar percentage to that found in other studies on infant education [11]. A total of 90.3% of the children who suffered rejection are boys [16], and we found that girls were more popular than boys; 60.7% compared to 39.3% [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…Several authors identify similar percentages of rejected students in the first years of primary education; 13% of students, according to Monjas et al [14], or 9.1% [15]. However, we found fewer studies on classroom sociometric typology in early childhood education, in which 8.1% of students are rejected [11]. It has also been found that this phenomenon mainly affects boys [16], with the latter being more likely to be victims of bullying than girls [17], who are generally more preferred in the classroom [15,16].…”
Section: Introductionmentioning
confidence: 40%
See 1 more Smart Citation
“…As a consequence, the measures towards attention to diversity are of enormous importance to adjust the pupils' teaching-learning process, as its lack of judgment is related with an increased risk of school failure or dropout [3]. For that reason, it is fundamental that in the educative field as well as with research, adequate evaluation instruments be available for such measures [7,16].…”
Section: Introductionmentioning
confidence: 99%